Parental Factors Associated with Rumination Related Metacognitive Beliefs in Adolescence - Chow, Ka-wai; Lo, Barbara C. Y. (Frontiers in Psychology, 2017)
An increasing number of research studies have suggested that metacognition is associated with individuals’ mental health. Specifically, metacognitive beliefs about rumination was proposed to link to the onset and maintenance of depression according to the metacognitive model of depression. The current study aimed to serve as a pilot study exploring how parents’ metacognitive beliefs and parenting characteristics are associated with rumination related metacognitive beliefs in adolescents. Eighty-five parent-youth dyads were invited to complete a set of questionnaires examining their metacognitive beliefs about rumination followed by a difficult puzzle task, in which parent- adolescent interaction patterns were recorded to examine the parenting style. Results found that parents’ and adolescents’ positive metacognitive beliefs about rumination were significantly associated with each other. In addition, parental negativity was significantly associated with adolescents’ positive metacognitive beliefs of rumination and parental over-involvement was marginally associated with adolescents’ negative metacognitive beliefs of rumination. The findings highlighted the association between parental factors and adolescents’ metacognitive beliefs about rumination. Implications on the prevention of adolescent’s depression were discussed.